1993
DOI: 10.1113/jphysiol.1993.sp019701
|View full text |Cite
|
Sign up to set email alerts
|

Na+ pump current‐voltage relationships of rabbit cardiac Purkinje cells in Na(+)‐free solution.

Abstract: SUMMARY1. The Na+ pump current (Ip) of isolated, single rabbit cardiac Purkinje cells in Na+-free solution was measured at 32-34 'C by means of whole-cell recording.2. The Ip amplitude was studied as a function of clamp potential (V,)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
(61 reference statements)
2
22
0
Order By: Relevance
“…Similarly, Ip activation by K+ is facilitated in cardiac ventricular mnyocytes (Nakao & Gadsby, 1989) and Purkinje cells (Bielen, Glitsch & Verdonck, 1993) superfused with Na+-free solution. Since the results presented so far revealed that activation of the Na+-K+ pUInp by K+-binding affects the interaction between DHO and the pumimp, we thought it miglht be interesting to studly the possiible effect of Na+ on the DHO-K+ Figs 1A, B, and 2A but Na+-free, choline-containing superfusion mnedia wAere applied to cells as well.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Ip activation by K+ is facilitated in cardiac ventricular mnyocytes (Nakao & Gadsby, 1989) and Purkinje cells (Bielen, Glitsch & Verdonck, 1993) superfused with Na+-free solution. Since the results presented so far revealed that activation of the Na+-K+ pUInp by K+-binding affects the interaction between DHO and the pumimp, we thought it miglht be interesting to studly the possiible effect of Na+ on the DHO-K+ Figs 1A, B, and 2A but Na+-free, choline-containing superfusion mnedia wAere applied to cells as well.…”
Section: Resultsmentioning
confidence: 99%
“…KSmall differences in the shape of the p-V relationships may be due to the different concentrations of the external pump activator cation used (cf. Bielen, Glitsch & Verdonck, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is helpful to realize that the mean values of the measured I,p are not significantly different from zero between -20 and -95 mV (Fig. 5) (Rakowski, Vasilets, La Tona & Schwarz, 1991;Omay & Schwarz, 1992) and freshly isolated rabbit cardiac Purkinje cells (Bielen et al 1993 …”
Section: Discussionmentioning
confidence: 99%
“…Figure 6D shows the exponential time course of the slow component. Bielen et al (1991aBielen et al ( , 1993 Fig. 4B and D).…”
Section: Solutionsmentioning
confidence: 99%